2019
DOI: 10.1177/2325967119868674
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Rotator Cuff Repair Techniques: Biomechanical, Functional, and Structural Outcomes

Abstract: There is substantial evidence indicating that double-row (DR) repair restores more of the anatomic rotator cuff footprint and is biomechanically superior to single-row (SR) repair. Transosseous-equivalent (TOE) techniques have shown biomechanical advantages when compared with traditional DR, including increased contact at the rotator cuff footprint, higher pressure at the tendon-bone interface, and increased failure strength. Several meta-analyses of evidence level 1 and 2 studies have shown a lower rate of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 60 publications
2
38
0
2
Order By: Relevance
“…Further biomechanical studies are needed to confirm whether the current procedure can fix SPR more firmly to the bone than the previously reported false-pouch closure technique. Previous biomechanical studies have shown that a wider contact area with the suture bridge technique has superior time-zero structural properties in rotator cuff repair [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further biomechanical studies are needed to confirm whether the current procedure can fix SPR more firmly to the bone than the previously reported false-pouch closure technique. Previous biomechanical studies have shown that a wider contact area with the suture bridge technique has superior time-zero structural properties in rotator cuff repair [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Controversy remains in terms of placing the anchors in a single-row or double-row arrangement [ 21 ]. Meier and Meier [ 22 ] suggested that DR suture anchor fixation provided significantly stronger initial strength than conventional SR repair, because DR suture anchor fixation consistently reproduces 100% of the original supraspinatus footprint, whereas SR suture anchor fixation reproduces only 46% of the insertion site [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The truth is, we presently lack the clinical data supporting this. Even with extensive evidence of advantages of certain techniques over others (e.g., double row over single row, transosseous equivalent), there is currently few highquality data supporting one technique over another, 5 let alone one suture material over another, leading to superior clinical outcomes. But in the end, there is little reason not to use a stronger suture material in a ligament or tendon repair.…”
Section: See Related Article On Page 708mentioning
confidence: 99%